BEING OF QUALITY OF FIRST OPENING OF PRODUCTIVE LAYERS WITH ANOMALOUS LOW PRESSURES - Коцкулич, Ярослав Степанович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Materials of the article allow to conclusion that high quality of opening of productive layers with anomalous low plast pressure can be attained at the scientifically grounded approach to the choice of types and properties of was thing liquids, and also method of opening of layers taking into account the concrete mountain-geological terms of the boring drilling.